Decentralized trigeneration in Wroclaw conditions - Reszewski, Stefan (Instal, 2025)
The article presents the possibilities of using absorption chillers powered by the district heating network for air conditioning of facilities instead of compressor refrigeration chillers. An analysis of the impact of such a solution on the efficiency of cogeneration is presented, using the example of the Kogeneracja S.A. power plant and the data obtained. The savings in fuel consumption resulting from the increase in cogeneration efficiency due to the implementation of distributed trigeneration were determined. In addition, the reduction of harmful emissions resulting from the change in the method of implementing the cooling effect using absorption units supplied by the district heating network instead of cooling units driven by electricity was determined.